Rheological evaluation of natural polysaccharide-based biopolymers through porous media - Gbonhinbor, Jeffrey Randy; Yelebe, Zekieni Robert; Yousuo, Digieneni; Agi, Augustine Aja (Springer Berlin Heidelberg, 2025)
Natural polysaccharide-based biopolymers have been utilized as practicable injectants in chemical enhanced oil recovery (CEOR) processes. Their subjective attributes and eco-friendly gains encourage preferential adaptation to hydrocarbon exploitation in contrast to synthetic polymers. Potential practicability of some biopolymers is devoid of mini-scale field assessment due to disregarded technicalities in CEOR operations. This study considers some highly tortuous formation samples subjected to single-phase flow of natural polysaccharide-based biopolymers. Two biopolymers were molecularly assessed using scanning electron microscopy (SEM), Fourier transform infrared (FTIR) spectroscopy, zeta potential (ZP), and X-ray diffractometry (XRD). Different solutions of individual biopolymers were prepared with varied concentration levels in different saline water configured at set temperatures. Rheological profiling for each formulation was scrutinized using known techniques in bulk and pore-scale rheological evaluations. This facilitated a multi-way analysis of variance (MANOVA) on corresponding microfluidic apparent viscosities and shear rates. Molecular assessment showed biopolymers were reactively stable polysaccharides with differing crystallinity and particle size not greater than 10 µm. Bulk rheological profiles of aqueous biopolymer formulations attest to shear thinning tendencies. Pore-scale rheology reaffirmed cassava starch solutions displayed better microfluidic rheological behavior in comparison with aqueous okra formulations. Early shear thickening profiles were detected by some biopolymer formulations which generally substantiates their viscoelastic nature. Optimized extrapolations of experimentally derived rheology put first critical shear rates for all formulations greater than 20 s−1. Statistical assessment identified injection rate as the most significant variable that influences computed microfluidic apparent viscosities and shear rates.